2016
DOI: 10.1002/ejic.201601140
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Preferentially Binds to Zinc Finger Proteins Containing C3H1 or C4 Motifs

Abstract: Cisplatin is a widely used anticancer drug for the treatment of a variety of human malignancies. It has been reported that cisplatin could react with a variety of zinc finger proteins (ZFPs), which results in structural perturbation followed by malfunction of the proteins. However, some other ZFPs were found to be unreactive to cisplatin. The difference in the reactivity of various ZFPs remains unclear. Here we investigated the reaction of cisplatin with ZFPs containing different zinc binding motifs (C2H2, C3H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…It has been reported that Ru compounds exhibited different reactivity to DNA or proteins; particularly, the selectivity of Ru‐agents varies dependent upon the target of biomolecules . The different types of zinc finger proteins, such as CCHH, CCHC, and CCCC domains, are known to have different reactivity to metallodrugs . In addition, the protein sequence and residues around zinc center also influence the reactivity of the protein.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Ru compounds exhibited different reactivity to DNA or proteins; particularly, the selectivity of Ru‐agents varies dependent upon the target of biomolecules . The different types of zinc finger proteins, such as CCHH, CCHC, and CCCC domains, are known to have different reactivity to metallodrugs . In addition, the protein sequence and residues around zinc center also influence the reactivity of the protein.…”
Section: Figurementioning
confidence: 99%
“…[23b] The different types of zinc finger proteins,s uch as CCHH, CCHC, and CCCC domains, are known to have different reactivity to metallodrugs. [7,28] In addition, the protein sequence and residues aroundz inc center also influencet he reactivity of the protein. For instance, the pstacking between aromatic residues of proteins and ligand of metal complexesc an enhance their reactions.…”
mentioning
confidence: 99%
“…18 It has been reported that the binding of many metallodrugs, such as arsenic, platinum, and ruthenium agents, to zinc-nger proteins induces the release of zinc ions from the proteins. [18][19][20] Here we observed that the reaction of Ru-1 also resulted in zinc release from PML (Fig. 4B).…”
Section: Ruthenium Complex Directly Binds To Pml and Disrupts The Promentioning
confidence: 89%
“…Truly, zinc ion replacement with gold, platinum, cobalt, and selenium complexes can disrupt ZnF protein binding to nucleic acids [ 90 ]. Further, cisplatin, a well-known platinum-based anti-cancer drug, can selectively bind to and cause structural perturbation of some ZnF motifs [ 91 ]. It remains to be tested whether any of the metal-based compounds can alter the biological functions of the ZC3H11A protein.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%